Basketball New Zealand Guidelines: Safe return to training for players in preparation for a condensed national basketball league season following covid19 restrictions - Bird, S. P.; Osborne, H.; King, L.; Belles, L.; Nolan, E. M; McLella, C. (New Zealand Journal of Sports Medicine, 2020)
The primary focus of the Basketball New Zealand guidelines is the safe return to training for players in preparation for competition. At the forefront of these guidelines is player health and wellbeing. This deals with both the physical and psychological preparation of players to compete in a condensed National League, and prevention of viral spread through common COVID-19 hygiene measures. We acknowledge the logistical constraints, and the difficulty to implement sport-specific training strategies under previous New Zealand Alert Levels,26 making it difficult to provide training solutions comparable to those adopted under normal circumstances. Fundamental objective assessments and ongoing subjective athlete monitoring is likely the best avenue to determine players readiness following reintegration to the training environment and during the returning to training/play phase.32 This provides an opportunity to individualise, recommend, implement, and modify daily training loads. Recovery strategies addressing muscular, neural, psychological, substrate recovery such as sleep hygiene, best nutrition practice, and psychological wellbeing have potential to improve athlete health and performance.6,14,33 Training trategies such as micro-dose loading and prehabilitation focused on high risk areas may improve physical and psychological readiness of players.32 While the proposed guidelines provide a framework for injury risk minimisation and safe return to training and competition, further to this, sports administrators and medical providers must remain aware of common COVID-19 symptoms and testing protocols as indicated by local resources, in the event of a positive case, to minimise spread among teams.